Pengabdian Kepada Masyarakat: Edukasi Anti-Bullying Melalui Media Komik dan Refleksi Diri Santri di RQ Badruttamam Bone - Nuratika, Nuratika (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Bullying behavior remains a potential issue within boarding-based educational environments, including Islamic boarding schools, thus requiring systematic preventive educational efforts. This community service program aimed to improve students’ understanding of the forms, impacts, and prevention of bullying through an interactive educational activity conducted at Rumah Qur’an Badruttamam. The implementation method consisted of three stages: preparation, implementation, and evaluation, carried out through material presentation, participatory discussions, educational comic media, and written reflection. The activity involved 68 students. The results showed that participants were able to identify various forms of bullying, with verbal bullying being the most frequently recognized, such as mocking, negative nicknames, and body-related insults. Students’ reflections indicated emotional impacts including sadness, fear, and low self-confidence due to experiencing or witnessing bullying. All participants expressed a commitment not to engage in bullying, as evidenced by written declarations. These findings indicate that visual, reflective, and participatory educational approaches are effective in improving awareness and understanding of bullying behavior. The program contributed to increased social literacy, character strengthening, and collective awareness to create a safe and harmonious boarding school environment. Therefore, anti-bullying education programs are recommended to be implemented continuously as a preventive strategy in student character development. Keywords: Bullying, Character Education, Students, Prevention, Boarding School